Gender-dependent difference in serum paraoxonase 1 levels of Hanwoo, Korean native cattle, and a positive association with meat quality - Jihyun Park; Jiwoo Kim; Sungwon Hwang; Ki Young Chung; Inho Choi; Chang Bon Choi; Jihoe Kim (Asian-Australasian Journal of Animal Sciences, 2019)
Objective Paraoxonase 1 (PON1), a calcium-dependent serum enzyme, has been shown to be involved in lipid metabolism. In this study, we examined the putative correlation of the serum PON1 level of Hanwoo, Korean native cattle, with gender and meat quality grade. Methods PON1 levels were estimated by determining the arylesterase and paraoxonase activities (AE and PO, respectively) in serum samples from Hanwoo individuals (n = 56). Serum PON1 levels were analyzed in different gender groups (female [n = 21], castrated male [n = 17], and male [n = 18]), and meat quality grades (≥1 [n = 23], 2 [n = 21], and 3 [n = 12]). Results Serum PON1 levels were similar in female (AE = 120±55 U/mL, PO = 84±43 mU/mL) and castrated male (123±44 U/mL, PO = 89±30 mU/mL), while male showed a significantly lower level (AE = 65±43 U/mL, PO = 44±34 mU/mL). Furthermore, analysis of serum PON1 levels in three different grades of meat quality showed similar levels in the grades ≥1 (AE = 118±49 U/mL, PO = 84±37 mU/mL) and 2 (AE = 116±54 U/mL, PO = 82±43 mU/mL), while the level was significantly lower in the grade 3 (AE = 58±35 U/mL, PO = 39±27 mU/mL) of lower meat quality. Conclusion We discovered the gender-dependent differences in serum PON1 levels of Hanwoo and a positive association of the serum PON1 level with meat quality. Results in this study suggest that PON1 would be a useful serum marker for preliminary screening of Hanwoo individuals with high-quality meat and applicable for genetic improvement.